Ways to Improve the Competitiveness of Agricultural Production in Kazakhstan - TIREUOV, Kanat M.; KERIMOVA, Ukilyay K.; TUREKULOV, Suleimen A. (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
Kazakhstan, which occupies the 9th place in the world and the 3rd place in the territory per capita, has great potential for the development of agriculture. There are 15 ha of land per inhabitant, including 1.3 ha of arable land. In recent years, gross agricultural output has exceeded 4.0 trillion tenge. The purpose of this study is to present the current state of agricultural activity in Kazakhstan and to search for effective ways to improve the quality and profitability of products manufactured by agricultural cooperatives. Improving the competitiveness of agricultural production in Kazakhstan can be achieved in several ways. As a result of the study, we presented the following methods: preserving resources, developing infrastructure, improving quality and expanding the range of products, improving sales quality and promoting products in the domestic and foreign markets, as well as introducing innovative technologies, as an extension of cooperation and integration.